KOMUNIKASI INTERPERSONAL ANTARA ORANG TUA DAN ANAK PENGEMIS DI PANTAI MUARO LASAK KOTA PADANG - Yetri Linovita; Desi Syafriani (Pusat Riset dan Inovasi Nasional, 2023)
The background of this study shows that there are a large number of beggars on Muaro Lasak beach, Padang City, both from children and the elderly. However, not all of the children who begged on the shores of Muaro Lasak Beach ordered their parents and some of their friends to join them. It is caused by a lack of communication between parents and children. Even indirectly the parents themselves tell their children to beg in order to get income. The type of research that the writer uses is a qualitative approach, with the intention of the researcher to describe by means of in-depth interviews with the object of research. The results of this study indicate that the large number of beggar children in Tapi Pantai Muaro Lasak, Padang City is caused by several factors, both from cultural factors, strength, emotions and context, self-esteem and self-awareness factors. The cultural activity factor that they carry out is no longer taboo but has become a habit that continues to develop and become a culture. This power factor causes the occurrence of children begging by their parents because they are in control at the location on Muaro Lasak Beach and become a strategy for children. The emotional factor is that they beg because of their own will and have been prohibited by their parents, but it does not rule out that they will stop begging on Muaro Lasak beach. the context factor refers to the environment, in this factor the environment is also important because there are children who beg only to follow their friends. The environment has a great influence on people's behavior. One self-esteem factor seeks attention from others because a lack of attention from parents can cause a child to seek attention from other people. The self-awareness factor of a beggar child who helps his parents' economy and the results they get will be given to his parents or grandmother. There are even barriers to interpersonal communication between parents and children that cause ineffective communication, namely process barriers, physical barriers, and emotional barriers.